2005
DOI: 10.1021/jp053224i
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Degree of Nematic Ordering within Dense Aqueous Dispersions of Charged Anisotropic Colloids by23Na NMR Spectroscopy

Abstract: Aqueous dispersions of Laponite, a synthetic clay neutralized by sodium counterions, are used as a model of charged anisotropic colloids to probe the influence of the shape of the particle on their organization within a macroscopic nematic phase. Because of the large fraction of condensed sodium counterions in the vicinity of the clay particle, (23)Na NMR is a sensitive probe of the nematic ordering of the clay dispersions. We used line shape analysis of the (23)Na NMR spectra and measurements of the Hahn echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 65 publications
8
26
0
Order By: Relevance
“…In the case of the quadrupolar relaxation mechanism, the intrinsic spectral density (J 1 Q, intrinsic (0)) is much higher than the two other components (J 0 Q, intrinsic (0) and J 2 Q, intrinsic (0)). Such a feature was previously evidenced by measurements of 7 Li and 23 Na NMR relaxation 71,72 in dense clay sediments and predicted by multiscale numerical modeling. 72 This appears logical as, despite their a priori differences, both types of experiments display fundamental similarities.…”
Section: Resultssupporting
confidence: 65%
“…In the case of the quadrupolar relaxation mechanism, the intrinsic spectral density (J 1 Q, intrinsic (0)) is much higher than the two other components (J 0 Q, intrinsic (0) and J 2 Q, intrinsic (0)). Such a feature was previously evidenced by measurements of 7 Li and 23 Na NMR relaxation 71,72 in dense clay sediments and predicted by multiscale numerical modeling. 72 This appears logical as, despite their a priori differences, both types of experiments display fundamental similarities.…”
Section: Resultssupporting
confidence: 65%
“…Such behavior was already reported for various quadrupolar nuclei confined within dense clay sediments. , , Under isotropic conditions (i.e., aqueous solutions), the three spectral densities quantifying the quadrupolar relaxation mechanism are identical, , leading to the same NMR relaxation rate, whatever the sample orientation into the static magnetic field (see eq ). By contrast, within heterogeneous samples, the relative enhancement of the m = 1 component of the quadrupolar relaxation mechanism may be used to probe the degree of nematic ordering even in the lack of detectable residual quadrupolar splitting. , …”
Section: Resultsmentioning
confidence: 99%
“…By contrast, within heterogeneous samples, the relative enhancement of the m = 1 component of the quadrupolar relaxation mechanism may be used to probe the degree of nematic ordering even in the lack of detectable residual quadrupolar splitting. 78,79 III.3. Spin-Locking Relaxation Measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Fewer experimental studies have examined the nanoseond to second molecular-scale dynamics of dissolved cations at smectite–H 2 O interfaces using NMR, ,, and there has been little experimental effort to understand the relationships between cation and H 2 O dynamics, particularly how they influence one another over a broad range of temperatures. , MD modeling of room-temperature cation diffusion in one- to three-layer smectite hydrates has shown that coefficients for continuous diffusion of Na + are 2 orders of magnitude slower than in bulk solution and that more restrictive jump diffusion of Cs + is up to 7 orders of magnitude slower than in bulk solution. ,, NMR relaxation rates yield Na + and Li + diffusion rates for dilute and dense smectite suspensions ,,,,− that are in general agreement with the MD results. We know of no modeling studies focusing on low-temperature cation dynamics, but a few variable-temperature NMR studies have provided insight at temperatures where cation dynamics are dominated by mechanisms such as direct site exchange or dynamic averaging by motion of the coordinating H 2 O. Laboriau et al report chemical exchange between Na + sites in smectites and suggest that Na + site exchange at paste levels of hydration occurs between sites that are different than those observed in “dry” or dilute suspension samples.…”
Section: Introductionmentioning
confidence: 99%